PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI INDUTRI MEUBEL BUKIR KOTA PASURUAN - Achmadi Akhimullah Febrianto; Wahyu Hidayat Riyanto; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2020)
This study is aimed at determining the effect of capital and labor variables on the amount of industrial furniture production in Bukir Sub-District, Gadingrejo District, Pasuruan City, the magnitude of the level of input and return to scale elasticity that occurred in the industry. This research used quantitative research, data obtained by questionnaire, and interview. The method used in sampling is to take a random sample of the entire population with a total sample of 42 furniture industries. The data analysis technique used is the Cobb-Douglas production function with multiple regression analysis. The results showed that capital and labor simultaneously affect the furniture industry's production with an F-value (0.0001<0.05). The result of the t-test showed that the capital variable partially has a significant effect on the production of the furniture industry with a value of prob (0.0393<0.05). The result of the t-test showed that the labor variable partially has a significant effect on the production of the furniture industry with a value of prob (0.0197<0.05). The magnitude of the elasticity of capital input is 0.401 and labor input is 0.664, the value is less than 1 so it is inelastic. Returning to scale showed that the furniture industry is on an increasing scale.